Consumer Behavior Changes Post Pandemic Covid-19 - Maryati , Tati (International Journal of Halal Research, 2020)
The Corona virus or Covid-19 which is unexpected will come to us, has an impact on health, economy and also humanity throughout the world and is able to fundamentally change the world. Supplements are disrupted because production is stopped, retail stores close, causing consumers to change their behavior, which had previously gone offline shopping. Not just shopping, when a pandemic, the way of thinking becomes different. Consumers around the world are looking for products and brands through new ways and new habits are formed. Online transactions focus more on basic products to make ends meet. The fact that Covid-19’s anti-virus has not been found raises concerns about disrupted health and the Government’s regulation to work and stay at home also raises concerns about disrupted businesses. Differences from habits and interests or preferences that are different for each person, provide different responses to the problems faced and solutions for the future. The habit of shopping offline has a tendency to continue for complementary products while food products are more directed towards offline. The rest eating habits at home can be continued because it provides more hygiene guarantees. The new habit of holding online meetings with distant relatives or colleagues will be increasingly considered given the many more positive things that can be obtained. Likewise with work problems, working from home is more interesting to consider because it is more efficient and effective and the results can be more productive. This new consumer behavior is adjusted to provide satisfaction for many parties, with the assistance of institutions or governments that oversee the security of supply and demand and maintain the stability of both.